The psychosocial impact of dental aesthetics and experiencing discrimination at a Peruvian public hospital among outpatients - Carbajal, Claudia (2022)
Aim To evaluate the association between outpatient's perceived psychosocial impact of dental aesthetics and experiencing discrimination at a Peruvian public hospital. Material and methods Cross-sectional study in a Peruvian public hospital, where 207 outpatients (18-30 years old) were surveyed. We asked participants about self-reported experiences of discrimination in the last six months at a Peruvian public hospital using a question from the Peruvian National Household Survey on Living Conditions and Poverty (ENAHO) 2017. We also measured the perceived psychosocial impact of dental aesthetics with the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ). Additionally, we evaluated age, sex, ethnicity, education, income, and reason for being discriminated against. Association was assessed with Poisson regression using a robust estimator of variance and reporting prevalence ratios with 95% confidence intervals in crude and adjusted models. Results About two out of every five participants having experienced discrimination at a Peruvian public hospital in the last six months. On our adjusted estimates, we found discrimination to be positively associated with two components of the psychosocial impact of dental aesthetics, which were social impact (PR 1.02, 95% CI 1.00-1.04) and the psychological impact (PR 1.07, 95% CI 1.04-1.10). Conversely, dental self-confidence (PR 0.96, 95% CI 0.93- 0.98) was negatively associated with discrimination. Conclusions The perceived psychosocial impact of dental aesthetics is associated with experiencing discrimination among outpatients from a Peruvian public hospital. We advocate for structural changes to address discrimination in healthcare spaces by corresponding governmental authorities.